Teaching Community Skills to Two Young Children with Autism Using a Digital Self-Managed Activity Schedule. Issue 4 (1st October 2016) - Cheung, Yvonne; Schulze, Kimberly A.; Leaf, Justin B.; Rudrud, Eric
ABSTRACT: The current study investigated the efficacy of a self-managed activity schedule to teach 2 participants how to effectively order food items from a local community bakery. 2 participants who were on the autism spectrum were taught to follow a task analysis that was displayed on an iPhone. We used a multiple baseline design across participants to evaluate the effectiveness of the teaching procedure. Results showed that the participants were able to order items, and this skill generalized to a novel bakery. The task analysis and iPhone were immediately withdrawn at a 2 to 5 week follow-up, and both participants were still able to effectively perform the steps of the task analysis without the use of prompts.